UI/UX Design Of Marketplace Service Mobile and Laptop Applications Using Design Thinking Method - Aqsa Arumdapta, Gemintang; Reisa Permatasari, Reisa Permatasari; Anindo Saka Fitri, Anindo Saka Fitri (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2024)
Inefficient repair services for damaged smartphones and laptops pose challenges for both users and service providers. This research answers this problem by designing a mobile application marketplace interface for smartphone and laptop repairs by prioritizing usability and user experience (UX). Design thinking methodology guides the development process, which involves user empathy, problem definition, ideation, prototyping, and testing. Iterative evaluation using usability testing and heuristic evaluation refines the design. The evaluation results of the final iteration showed a Learnability score of 96.6%, Efficiency 98.63%, Memorability 95%, Error 0.232, and Satisfaction 83.23 from technicians, as well as Learnability 93.3%, Efficiency 85.23%, Memorability 85%, Error 0.202, and Satisfaction 83.23 from customers, with success and very good qualifications. Heuristic evaluation by UI/UX experts further validates the usability of the design. This research concludes that the design thought approach has succeeded in creating a user-friendly marketplace interface for smartphone and laptop repair services. The app's high usability and positive reception from technicians and customers highlight its potential to simplify the repair process and increase overall customer satisfaction.